Islamic English: Is there a need? - Othman, Khairiah; Abdul Malik, Faridah; Ismail, anis Izzati (2016)
A significant rise in the number of English-speaking Muslims around the world calls for more attention on the proper usage of Islamic terms in the English language. Popularized by al-Faruqi (1986), Islamic English refers to the English language modified to enable Muslims to carry Islamic proper names, nouns, meanings and concepts without distortion. This paper aimed to examine Islamic words and concepts utilized by Maher Zain in his English Islamic songs. Qualitative data collection was employed. The findings indicate the presence of Arabic words and concepts in his songs mainly due to the absence of equivalent English words and lack of accurate translation, hence the need for Islamic English.